Aspectos de la relación entre thalurania furcata colombica (aves trochilidae) y las flores en que liba, en un bosque subandino (1986)
Between April and September 1983 observations were made on the relations between Thalurcnia furcata colombica and flowers in the laguna de Pedro Palo area (Cundinamarca, Colombia). The hummingbird was seen visiting 15 species of plants (beloging to 13 families) situated mainly on the edge of forest, among which the following species showed a high degree of ornithophily: Besleria solanoides (Gesneriaceae), Bomarea racemose (Amaryllidaceae), Cornutia odorata (Verbenaceae), Erythrina edulis (Fabaceae) and Palicourea popayanensis (Rubiaceae). Nectar was available for hummingbirds during the six months of study. Although males and females of the species had similar habitat and food preferences, a relatively small number of agressive encounters between them was recorded. Three mechanisms were recognized which contributed to reduce these encounters: 1. a difference in foraging strategies, males being predominantly territorial and females generalists (behaving as territorial or "trapliners" according to circumstances) ; 2. differences in the temporal organization of their foraging activity through the day; 3. differences in spatial organization, males and females tending to exploit different parts of the same plant.  Thalurania furcata defended its feeding territories against individuals of its own and other species of hummingbirds (Chlorostilbon gibsoni, Coeliqena prunellei and others), flower-piercers (mainly Dlglossa sittoides), and butterflies.